2001
DOI: 10.11650/twjm/1500407347
|View full text |Cite
|
Sign up to set email alerts
|

ON STABILITY OF THE EQUAIONS Bu0(t) = Au(t)

Abstract: The stability of solutions of the equation Bu 0 (t) = Au(t) is considered, where A and B are closed linear operators on a Banach space. Under the well-posedness condition it is proved that if the imaginary part of the spectrum of the pencil (¸B ¡ A) is countable, then a bounded uniformly continuous solution u(t) of the equation is asymptotically almost periodic if and only if the functions e ¸tu (t), (¸2 iR), have uniformly convergent means. A condition of exponential stability also is given when the generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The pyrolysis products of dimethylamphetamine have been studied by GC/MS, headspace GC/MS, and LC/ESI/MS (348). Methamphetamine and other related stimulant samples were profiled using headspace SPME/ GC/MS (349,350), capillary GC (351), and GC/MS, GC/PIMS, and GC/MS/MS (352). The combined use of δ 2 H, δ 13 C, and δ 15 N isotopic data along with 2 H NMR was used to study the synthetic pathways used in the preparation of MDA and N-substituted homologues (353).…”
Section: Drugs and Poisonsmentioning
confidence: 99%
“…The pyrolysis products of dimethylamphetamine have been studied by GC/MS, headspace GC/MS, and LC/ESI/MS (348). Methamphetamine and other related stimulant samples were profiled using headspace SPME/ GC/MS (349,350), capillary GC (351), and GC/MS, GC/PIMS, and GC/MS/MS (352). The combined use of δ 2 H, δ 13 C, and δ 15 N isotopic data along with 2 H NMR was used to study the synthetic pathways used in the preparation of MDA and N-substituted homologues (353).…”
Section: Drugs and Poisonsmentioning
confidence: 99%
“…It allows rapid sample collection, does not use organic solvents, is easy to use, and is selective. 29 SPME has been used with GC-MS for qualitative analysis of headspace vapors of surface wipes 30,31 hair, 32 and street methamphetamine 33,34 but has not been evaluated for determination of methamphetamine in indoor air. Our preliminary studies showed that SPME met the criteria of sensitivity and rapidity, but in its passive mode SPME bres could be exposed to varying volumes of air depending on air currents within the premises.…”
Section: Introductionmentioning
confidence: 99%